The PROSIT-BIO Cohort: A Prospective Observational Study of Patients with Inflammatory Bowel Disease Treated with Infliximab Biosimilar. Issue 2 (13th January 2017) - Fiorino, Gionata; Manetti, Natalia; Armuzzi, Alessandro; Orlando, Ambrogio; Variola, Angela; Bonovas, Stefanos; Bossa, Fabrizio; Maconi, Giovanni; D'Incà, Renata; Lionetti, Paolo; Cantoro, Laura; Fries, Walter; et al.
Abstract : Article first published online 13 January 2017. Abstract : Background: Few data are available on the safety and efficacy of infliximab biosimilar CT-P13 in patients with ulcerative colitis and Crohn's disease. Methods: A prospective, multicenter, cohort study using a structured database. Results: Consecutive patients (313 Crohn's disease and 234 ulcerative colitis) were enrolled from 31 referral centers; 311 patients were naive to anti–tumor necrosis factor alpha, 139 had a previous exposure to biologics, and the remaining 97 were switched to CT-P13 after a mean of 18 ± 14 infusions of infliximab. The mean follow-up was 4.3 ± 2.8 months, and the total follow-up time was 195 patient-years. After 2061 infusions, 66 serious adverse events were reported (12.1%), 38 (6.9%) of them were infusion-related reactions. The biosimilar had to be stopped in 29 (5.3%) cases for severe infusion reactions (8 naive, 19 previous exposed, and 2 switch), and in further 16 patients (2.9%) for other serious adverse events. Infusion reactions were significantly more frequent in patients pre-exposed to infliximab than to other anti–tumor necrosis factor alpha (incidence rate ratio = 2.82, 95% CI: 1.05–7.9). The efficacy of the biosimilar was evaluated in 434 patients who received treatment for at least 8 weeks, using time-to-event methods for censored observations: 35 patients were primary failures (8.1%). After further 8, 16, and 24 weeks, the efficacy estimations were 95.7%, 86.4%, and 73.7% for naive, 97.2%, 85.2%, and 62.2% for pre-exposed, and 94.5%, 90.8%, and 78.9% for switch, respectively (log-rank P = 0.64). Conclusions: Although no direct comparison was performed, preliminary data on efficacy and safety of CT-P13 were in line with those of infliximab.